Insights for a Rapidly Changing World : IEG 2020 Annual Report - Independent Evaluation Group (World Bank, Washington, DC, 2020)
For the Independent Evaluation Group (IEG), fiscal year (FY) 20 was a year of both internally and externally driven reform. IEG began the year with a mission to listen to the needs of our clients and stakeholders and improve our methods, relationships, and products to increase the relevance and value of our evaluative work. Thus, when the coronavirus pandemic (COVID-19) struck in the spring of 2020, IEG was already mobilized to respond to the World Bank Group’s critical needs with agility, flexibility, and innovation. The regular work program included evaluations of Bank Group convening power, country programs in Albania and the Philippines, irrigation, and education. Though before the pandemic, IEG offered just-in-time learning and on-demand learning engagements, the pandemic pushed us to double our efforts by mining our rich data archives to provide important lessons on Bank Group responses to past public health crises and collect knowledge in an online COVID-19 library. FY21 will continue challenging IEG to respond to rapidly changing pandemic conditions, produce just-in-time insights to help decision-making, and evaluate projects and programs with the same rigor as ever. We are committed to finding new ways of sharing knowledge, learning, and evaluating what works in the World Bank Group.